Influences of friction stir welding on the microstructure, mechanical and corrosion behaviour of AL-ZN-MG aluminium alloy 7039 (Engineering Review, 2015)
This paper presents the influence of friction stir welding (FSW) on the microstructure, mechanical and corrosion behavior of precipitation hardening Al-Zn-Mg alloy AA7039. The microstructure of weld joints was investigated using an optical microscope. The grains in weld nugget zone (WNZ) and thermo-mechanically affected zone (TMAZ) of weld joints were finer than in the base metal and a reverse trend was observed for heat affected zone (HAZ). Mechanical properties of friction stir weld joints were determined by tensile and micro hardness test. The ultimate tensile strength of weld joints was found approximately equal to the base metal while yield strength and ductility of weld joints were found lower than in the base metal. HAZ of weld joints was more susceptible to corrosion than WNZ, TMAZ and base metal. The HAZ exibits the highest current density followed by the base metal.